2013
DOI: 10.1093/jiel/jgt026
|View full text |Cite
|
Sign up to set email alerts
|

The Challenge of Cooperation: Regulatory Trade Barriers in the Transatlantic Trade and Investment Partnership

Abstract: The challenge of cooperation: regulatory trade barriers in the transatlantic trade and investment partnership.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 0 publications
0
48
0
2
Order By: Relevance
“…It was founded to deal with a major problem identified by its members, that is, competitiveness is hampered on both sides by excessive regulation and by differences between the EU and USA regulatory systems (Egan, 2003). The organization, now the Trans-Atlantic Business Council, had some early success with mutual recognition agreements in areas such as telecommunications equipment, some medical devices, and other limited product areas (Lester, and Barbee 2013). However, the efforts seem to have lost momentum in recent years.…”
Section: The Regulatory Trade Barriers In Usa -Eu Foreign Trade Policymentioning
confidence: 99%
See 4 more Smart Citations
“…It was founded to deal with a major problem identified by its members, that is, competitiveness is hampered on both sides by excessive regulation and by differences between the EU and USA regulatory systems (Egan, 2003). The organization, now the Trans-Atlantic Business Council, had some early success with mutual recognition agreements in areas such as telecommunications equipment, some medical devices, and other limited product areas (Lester, and Barbee 2013). However, the efforts seem to have lost momentum in recent years.…”
Section: The Regulatory Trade Barriers In Usa -Eu Foreign Trade Policymentioning
confidence: 99%
“…It is not clear how existing WTO rules -either the TBT or SPS agreements, or even more general rules such as the GATT or the GATS -are insufficient in this area. These rules draw a delicate balance between imposing international disciplines on trade measures and respecting national autonomy (Lester, and Barbee 2013 Indicated that an international standard, guideline or recommendation was applicable to the notified measure (Chart 4). Of these, 80% indicated that the proposed measure was in conformity with the existing international standard.…”
Section: The Regulatory Trade Barriers In Usa -Eu Foreign Trade Policymentioning
confidence: 99%
See 3 more Smart Citations